Hysterectomy: An Analysis of 162 cases in Dhaka National Medical Institute Hospital - Kobra, Khodeza Tul; Begum, Arzumanth Ara; Shova, Nazneen; Begum, Rashida (Journal of Dhaka National Medical College & Hospital, 2015)
Objective: To find out the indications, operative and post operative complications of Hysterectomy in women with benign pelvic diseases, with an aim to improve management at our unit. Place and duration of the study: This study was conducted in the department of Obstetrics and Gynaecology, Dhaka National Medical Institute Hospital during the period from July 2012 to June 2013. Materials and Methods: A hospital based prospective study was conducted in all patients undergoing hysterectomy for benign diseases who were followed up from the time of admission to the time of discharge and two weeks thereafter. Indications, routes of hysterectomy, intra & post operative morbidities during hospital stay, and two weeks after discharge were noted. We also compared the complications of total abdominal versus vaginal hysterectomy. A total of 162 patients who had hysterectomy were available for analysis. Among them 110 had total abdominal hysterectomy (N=110) and 52 patients underwent vaginal hysterectomy (N=52). Results: Total numbers of Hysterectomies performed were 162. Out of them 110 were total abdominal and 52 were vaginal hysterectomies. The principal indication for the vaginal hysterectomy was uterine penlapse (84.7%), while the most common indication for the total abdominal hysterectomy was uterine fibroid (53.6%). The overall complications rates were (39.04%) and (28.84%), in women who underwent total abdominal and vaginal hysterectomies respectively. Intraoperative complications were (12.96%). Febrile morbidity was the most common post operative complications in (8.64%). Urinary tract infections remained the most common febrile morbidity. There were two cases of reactionary haemorrhage in abdominal hysterectomy and one case of secondary haemorrhage in vaginal hysterectomy. Wound infection was found in 19 (17.3%) cases of abdominal hysterectomy. Conclusion: Vaginal hysterectomy is associated with less intraoperative and postoperative complication mes than total abdominal hysterectomy. J. Dhaka National Med. Coll. Hos. 2015; 21 (02): 10-14